fit2dive - A field test for assessing the specific capability of underwater fin swimming with SCUBA - Steinberg, F.; Drager, T.; Steegmanns, A.; Dalecki, M.; Roschmann, M.; Hoffmann, U. (International Journal of Performance Analysis in Sport, 2011)
Exercise modalities such as cycle ergometry do not mimic the specific movements of fin swimming underwater. Therefore, there is a need to develop a specific diving capability assessment procedure. The purpose of the study was the application of a standardized field test to assess and rate underwater swimming performance. The fit2dive-test consists of an incremental protocol that is performed in a pool (<5 m depth). The underwater swimming speed is increased stepwise by 0.2 m·s-1, starting with 0.4 m·s-1 until the subject's subjective exhaustion is attained. Time of break-off (fit2dive-time), swimming technique (e.g. range of motion (ROM) of hip and knee joints) and equipment configuration was recorded via a standardized checklist. Subjects with the highest hip and knee flexion had lower fit2dive-times (373 ± 119 s; p<0.01) than those in the normal hip and knee flexion ROM category (448 ± 104 s). Further, divers using full foot fins had significantly higher (p<0.001) fit2dive-times (474 ± 97 s) than divers with adjustable strap fins (375 ± 104 s). The fit2dive test indicates the specific capability of underwater fin swimming. The results allow identifying weak factors such as underwater swimming technique or equipment configuration.